Ski resorts in crisis and territorial construction in French Catalonia - Vincent Vlès (Revue de Géographie Alpine)
The efficiency of inter-municipal relations in regenerating or restructuring the economy of mountain tourist areas is well suited to an analysis in terms of governance. Focussing on the negotiation, consultation and cooperation processes between the public and private spheres, and associated networks of actors, provides an opportunity to assess the ties of solidarity in the management of crises. More specifically, this study examines inter-municipal relations in the context of the crisis now facing many small ski resorts in the Pyrenees, where declining snowfalls may lead to the dismantling of facilities or their adaptation to a hypothetical “4-season tourism”.The manner in which inter-municipal governance of the tourism resource is implemented in this context reveals fractures among the different actors relating to the management of jobs, housing, interests, resources, the issues at stake, and representations. Inter-territorial dynamics results in different types of cooperative arrangements and nested management systems that remain isolated, each covering competing projects. In the 11 Pyrenean ski resorts of French Catalonia, the different types of governance often remain narrowly delimited and compartmentalised, and inter-municipal cooperation takes place without any real democratic discussion with the resident population. Since debate is very rare, inter-municipal relations are at pains to bring about consensus between decision-makers on how to save the local ski areas threatened with permanent closure by a structurally deficient snowfall.